2008
DOI: 10.1097/brs.0b013e318163f9ee
|View full text |Cite
|
Sign up to set email alerts
|

Use of C-Reactive Protein After Spinal Surgery

Abstract: CRP is more applicable, predictable, and responsive in the early postoperative period compared with ESR. The postoperative kinetics of CRP derived in this study seems to be conserved regardless of operation, magnitude, or region. Knowledge of the kinetics allows assessment of the degree of difference between actual and expected values. Using a second rise or failure to decrease as expected for CRP is sensitive for infection. A negative test is reassuring that infection is unlikely.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(42 citation statements)
references
References 29 publications
2
39
1
Order By: Relevance
“…Several studies have reported the usefulness of this predictor and mentioned that the combination of normal CRP, ESR, and WBC levels reliably predicts the absence of infection after elective surgery5,10,12,18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have reported the usefulness of this predictor and mentioned that the combination of normal CRP, ESR, and WBC levels reliably predicts the absence of infection after elective surgery5,10,12,18).…”
Section: Discussionmentioning
confidence: 99%
“…Takahashi et al16) found that the post-operative CRP reached its peak on day 2 and remained abnormally elevated even after six weeks. And, Mok et al12) tried to derive the normal kinetics of CRP, opening the way for recognition of deviations that may indicate a complication. The kinetics seems to be conserved regardless of operation, magnitude, or region.…”
Section: Discussionmentioning
confidence: 99%
“…However, CRP peaks to a greater extent in patients with infection, but this peak can also be associated with blood loss, pre-operative CRP, and surgery in the lumbar region compared with surgery elsewhere in the spine. 20 In a series of 348 patients undergoing spinal surgery, when CRP levels were assessed at Days 1, 3 and 5 as part of the work-up to diagnose SSI, Kang et al found that elevated CRP levels had sensitivity and specificity of 100% and 97% for infection, respectively, but the positive predictive value was only 31%. 21 Fouquet et al noted that non-infected patients had significantly lower ESR and CRP levels at diagnosis and at four weeks follow-up.…”
Section: Inflammatory Markers and Imagingmentioning
confidence: 98%
“…Although it is known that CRP rises as a response to surgical tissue damage even in the absence of clinical infection [7][8][9] …”
Section: Elevation Of C-reactive Protein Levelsmentioning
confidence: 99%
“…Although mainly used by clinicians to screen for infection, serum CRP physiologically rises following surgical procedures due to the inflammatory cascade triggered by surgical tissue damage, even in the absence of infection [7][8][9].…”
Section: Introductionmentioning
confidence: 99%